Strategy Of MSMES Development Based On Shariah Economy In The Digital Era: Case Study Of Small Business In Morombuh Village - Alfarisi, Salman; Susetyo, Achmad Budi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the development strategies of sharia-based Micro, Small, and Medium Enterprises (MSMEs) in the digital era, using a case study of small businesses in Morombuh Village. The research is grounded in the urgency of strengthening MSMEs not only as resilient economic actors but also as entities aligned with Islamic values. A qualitative descriptive approach was employed, using observation, in-depth interviews, and documentation. The study focuses on identifying forms of social accommodation, the implementation of sharia principles in business practices, and the challenges and opportunities presented by digital transformation. The findings reveal that the development of sharia-based MSMEs in Morombuh occurs organically through the role of three key social actors: religious leaders and Islamic boarding schools as moral and spiritual guides, families as sources of technical and emotional support, and local communities as facilitators of digital literacy and market access. Despite challenges such as low digital literacy, weak business management, and limited access to sharia-compliant financing, MSME actors demonstrate significant potential for growth through strong values, social solidarity, and gradual technological adaptation. In conclusion, the development of sharia-based MSMEs requires a contextual, collaborative, and value-oriented approach as its foundational strategy.